Analisis biaya dan efektivitas WhatsApp Blast terhadap respons pelanggan dengan regresi berantai. - ardiningrum, Talitha widyadhana; Alam, Syariful; Sanjaya, Leonard Putra; Masykur, Alia Azizah; Dewi, Selvy Kirana (Universitas Multi Data Palembang, 2025)
This research analyzes the effectiveness of sending broadcast messages through the Cakraflash service at MH Thamrin University in the period from 8 July 2024 to 3 September 2024. This research was conducted because of the importance of understanding audience response in supporting digital communication strategies. The data used includes the number of messages sent, delivered, read, and replied. The chain regression analysis method was used to identify the relationship between these variables. The results showed that each stage of message delivery, from delivered to replied, significantly influenced each other. An increase in the number of messages received and read tends to increase the number of messages replied, which is an indicator of successful information delivery. The conclusions of this study provide important insights for universities to develop more effective, data-driven digital communication strategies based on audience response. Keywords— Chain Regression, Broadcast Messaging, Data Processing Complexity